Electron Stopping Power in Liver, Lung and Kidney Tissues: A Systematic Review - Niran Ali; Alaa Akon (Journal of Health and Biology, 2026)
The electron stopping power represents an essential physical factor in medical physics. This quantity is responsible for the rate of electron energy loss during passing through biological materials. Exact data on the electron stopping power play a critical role in dosimetry, treatment planning, Monte Carlo simulation, and protection against radiation. In this review, various publications on the electron stopping power in human liver, lung, and kidney tissues are presented and compared. Fifteen scientific papers dealing with the issue under discussion have been analyzed within the period from 2000 to 2026. The different types of computer simulations, including Monte Carlo simulations, Hartree-Fock-Roothaan wave functions, Bethe analytical model, dielectric-response model, and dual-energy computed tomography (DECT), are included in the review. It can be stated that the electron stopping power was significantly influenced by the density of the medium, the chemical composition of the tissue, the energy of electrons, and the density of the electrons. Lung tissue had lower stopping-power values than those of the liver and kidney due to the lower density of this material. The values of the electron stopping power were relatively high for kidney and liver. The majority of the results found in the paper were in agreement with the internationally approved databases such as NIST ESTAR.